GAGASAN PENAMBAHAN KEWENANGAN CONSTITUTIONAL PREVIEW KEPADA MAHKAMAH KONSTITUSI DALAM PROSES PENGESAHAN PERJANJIAN INTERNASIONAL - Reza, Mohamad (JURNAL ILMU HUKUM AKTUALITA, 2025)
The results show that currently, Indonesia has not provided special arrangements regarding the legal status of the Ratification Law. In fact, both materially and formally, the Ratification Law is different from laws formed by the DPR and the President. The absence of a special regulation regarding the Law of Ratification has caused legal polemics relating to its enforcement in Indonesia. The Consti-tutional review mechanism of the Ratification Law brings new legal polemics because it has the potential to cause the termination of binding to international agreements. Unilateral termination of bind-ing to international treaties is a form of disobedience to interna-tional law and will create state responsibility. The constitutional preview mechanism by the Constitutional Court turns out to be a solution in maintaining the constitutional rights of citizens and compliance with international law. The product of this mechanism can be a decision that tests the constitutionality of the Ratification Law with a follow-up in the form of a reservation at the stage of binding to the agreement without having to terminate the binding when the ratified international agreement has entered into force for the parties. Hasil penelitian menunjukkan bahwa saat ini, Indonesia belum memberikan pengaturan khusus mengenai status hukum Undang-undang Pengesahan. Padahal, baik secara materiil dan formil, Un-dang-undang Pengesahan berbeda dengan Undang-undang yang dibentuk oleh DPR dan Presiden. Ketiadaan pengaturan khusus mengenai Undang-undang Pengesahan menyebabkan polemik hukum yang berkaitan dengan pemberlakuannya di Indonesia. Mekanisme Constitutional review terhadap Undang-undang Pengesahan membawa polemik hukum baru karena berpotensi un-tuk menyebabkan pengakhiran pengikatan diri terhadap perjanjian internasional. Pengakhiran pengikatan diri secara sepihak terhadap perjanjian internasional merupakan bentuk ketidaktaatan terhadap hukum internasional dan akan melahirkan tanggungjawab negara. Mekanisme constitutional preview oleh Mahkamah Konstitusi tern-yata menjadi Solusi dalam menjaga hak konstitusional warga negara dan ketaatan terhadap hukum internasional. Produk dari mekanisme ini dapat berupa putusan yang menguji konstitusionalitas Undang-undang Pengesahan dengan tindak lanjut berupa reservasi pada tahapan pengikatan diri terhadap perjanjian tanpa harus mengakhiri pengikatan diri ketika perjanjian internasional yang telah disahkan telah berlaku bagi para pihak